Tellurium(II)/Tellurium(III)‐Catalyzed Cross‐Dehydrogenative C−N Bond Formation. Issue 12 (4th February 2021) - Cremer, Christopher; Goswami, Monalisa; Rank, Christian K.; de Bruin, Bas; Patureau, Frederic W.
Abstract: The Te II /Te III ‐catalyzed dehydrogenative C−H phenothiazination of challenging phenols featuring electron‐withdrawing substituents under mild aerobic conditions and with high yields is described. These unexpected Te II /Te III radical catalytic properties were characterized by cyclic voltammetry, EPR spectroscopy, kinetic experiments, and DFT calculations. Abstract : A Te II /Te III ‐catalyzed dehydrogenative C−H phenothiazination of challenging phenols proceeds under mild aerobic conditions and with high yields. These unexpected Te II /Te III radical catalytic properties were characterized by cyclic voltammetry, EPR spectroscopy, kinetic experiments, and DFT calculations.